The Optimal Cash Balance Proposition: Maurice Allais' Priority - Baumöl, William J.; Tobin, James (Journal of Economic Literature, 2016)
Maurice Allais' well-deserved Nobel Prize fortuitously brought to our attention an injustice inadvertently done him, to which we were unknowing accessories. For years the literature has ascribed to us the parentage of the transactions-cost model of optimal cash balances, with its notorious square-rootformula derivedfrom inventory theory.' Recently, we found that its essence is contained in Allais' 1947 Economie et Interet (pp. 238-41). As Jacob Viner used to say, no matter to what source the origin of an economic proposition is ascribed, someone is sure to come up with an earlier one. In any event, here is a translation of the pertinent passages. Allais describes the model in footnotes (11) and (12) to the following text (pp. 238-41):